Pengaruh Konsentrasi Kepemilikan, Penggeseran Risiko dan Pentransferan Sumber Daya Trhadap Ekspropriasi Pemegang Saham Minoritas Perusahaan Pengakuisisi: Pengujian Empiris Terhadap Pergeseran Konflik Keagenan - ETIK KRESNAWATI (The Indonesian Journal of Accounting Research, 2013)
This study provides empirical evidence of agency conflict shifting (La Porta et al. 1998, 1999) by investigates the influence of ownership concentration, risk shifting and tunneling on expropriation of acquirers’ minority shareholders. Sample in this study consist of 40 non financial and banking companies which perform internal acquisition during 1993-2002. Consistent with earlier prediction, the higher risk shifting, the higher expropriation of acquirers’ minority shareholders. Conversly, the evindences that ownership concentration does not significantly influence on, and tunneling has significantly negative influence on expropriation of acquirers’ minority shareholders are not consistent with ealier predictions. Additional test of dividend payment show that firm decreased the paid dividend to shareholders after performing internal acquisition. One of cause the decreasing is the existence of specific boundaries in debt contract to fund internal acquisition. These support agency conflict shifting prediction.